2010
DOI: 10.1111/j.1600-6143.2010.03209.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Desferrioxamine on Encapsulated Human Islets—In Vitro and In Vivo Study

Abstract: As many as 2000 IEQs (islet equivalent) of encapsulated human islets are required to normalize glucose levels in diabetic mice. To reduce this number, encapsulated islets were exposed to 100 lM desferrioxamine (DFO) prior to transplantation. Cell viability, glucoseinduced insulin secretion, VEGF (Vascular endothelial growth factor), HIF-1a (Hypoxia inducible factor-1 alpha), caspase-3 and caspase-8 levels were assessed after exposure to DFO for 12, 24 or 72 h. Subsequently, 1000, 750 or 500 encapsulated IEQs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…It seems possible that an accelerated rise in HIF-1 alpha during hypoxia could lessen damage afflicted by hypoxia. Such notion is in line with the observation that forced over-expression of HIF-1 alpha improved the results of beta cell transplantation [31], [32]. As to effects on AMPK this parameter which is sensitive to changes in metabolism was enhanced by diazoxide in response to hypoxia, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…It seems possible that an accelerated rise in HIF-1 alpha during hypoxia could lessen damage afflicted by hypoxia. Such notion is in line with the observation that forced over-expression of HIF-1 alpha improved the results of beta cell transplantation [31], [32]. As to effects on AMPK this parameter which is sensitive to changes in metabolism was enhanced by diazoxide in response to hypoxia, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…Based on the hypoxia-induced rise in basal insulin release that we observe for nonencapsulated islets, one possible explanation could be that islets within the microcapsule are subjected to mild hypoxia, which subsequently gives rise to the basal secretion. Data from Vaithilingam et al could support such notion since pretreatment with the hypoxia-mimicking desferrioxamine agent induces slightly elevated basal insulin secretion [25]. …”
Section: Discussionmentioning
confidence: 99%
“…At first glance this finding in nonencapsulated islets is paradoxical, since treatment of human islets with the hypoxia-mimicking agent desferrioxamine increased the expression of VEGF [25]. However, a study with islets indicated that a 48 h culture in normoxia increased VEGF mRNA and protein to an extent that further increase was not observed after hypoxia [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alginates microcapsules cross-linked with Ca 2þ or Ba 2þ are used successfully in both allograft and xenograft settings without the need for anti-rejection drugs, at least in rodents, with recipients becoming normoglycaemic (Silva et al, 2006). Previously, we have demonstrated successful encapsulation of human and foetal pig islets into simple barium alginate microcapsules and established their function in vivo (Foster et al, 2007;Vaithilingam et al, 2010). Recently, a phase 1 clinical trial by the Sydney group using barium alginate microcapsules showed that allografting of microencapsulated human islets is safe although only a minor clinical benefit was observed.…”
Section: Introductionmentioning
confidence: 96%